Analisis Ketidakkonsistenan Guru dalam Penggunaan Lembar Kerja Peserta Didik (LKPD) pada Pembelajaran di MIN 6 Aceh Utara - Syarifah Salsabila; Julrissani Julrissani; Siti Nurhaliza; Rizaul Qadri; Azizah Wesy Ara (IEC: Journal of Educational Innovation, 2026)
Teachers' inconsistency in using Student Worksheets (LKPD) during instruction at Madrasah Ibtidaiyah (MI) often poses a serious obstacle to the implementation of the Merdeka Curriculum, even though schools have provided adequate digital facilities. This study aims to critically analyze the factors causing this inconsistency and to evaluate the role of managerial supervision in addressing it. A qualitative approach using descriptive methods was employed through semi-structured interviews with teachers and the principal at MIN 6 Aceh Utara to obtain in-depth data on the pedagogical realities in the field. The results reveal a paradox between the school’s mature administrative readiness and instructional practices that remain sporadic. This inconsistency is driven by a heavy administrative workload, low digital literacy among teachers, and supervisory practices that tend to be corrective-administrative rather than supportive. This study implies the need to transform managerial supervision toward a clinical model based on peer mentoring within professional learning communities to strengthen teachers’ commitment and technical competencies. Redesigning a collaborative work culture has proven more effective in promoting consistent use of digital worksheets than formal reprimands, thereby creating a more adaptive and meaningful learning ecosystem.